Conceptual Review of Artificial Intelligence Over Reliance: Opportunities and Challenges for Employee Competencies - Apida Apida; Riska Dhenabayu; Abidah Ardelia; Aulia Kartika; Fathiya Fairuz Shafa Mahfuzhah; Nadiya Nafisa Az Zahra; Ika Diyah Candra Arifah (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to conceptually examine the phenomenon of AI over-reliance and its impact on employee competence in the digital era, particularly in human resource management. Research Methodology: A Systematic Literature Review (SLR) was conducted using 15 scientific articles selected for their relevance to AI over-reliance and human resource competencies. Results: The findings revealed that over-reliance on AI stems from four main factors: the perception of AI as a neutral authority, low AI literacy, automation bias that fosters excessive trust in technology, and system designs that discourage reflective user engagement. These factors contribute to reduced cognitive abilities, such as critical thinking and independent judgment, while diminishing human involvement in decision making. Furthermore, over-reliance on AI raises concerns about job displacement anxiety and promotes deskilling across sectors. Conclusions: Overreliance on AI challenges employee competence and decision-making capacity, necessitating strategic responses in system design, digital literacy enhancement, and human-AI collaboration frameworks. Limitations: This conceptual study is based solely on a literature review, limiting its empirical generalizability and contextual depth. Contributions: This study contributes to a deeper understanding of AI over-reliance and its implications for human resource management. This study offers insights for organizations to mitigate the negative effects of AI while leveraging it to enhance employee competence.